Indonesia : Toward Universal Access to Clean Cooking - World Bank (Washington, DC, 2013)
Indonesia's household cooking fuels have undergone a dramatic shift in recent years, owing primarily to the government's highly successful Kerosene-to- Liquefied Petroleum Gas (LPG) Conversion Program; yet the impact in poorer rural areas has been limited. Switching to LPG, electricity, and other modern fuels would be the most effective way to achieve clean cooking solutions, but these fuels are expensive, requiring costly stoves and delivery infrastructure that are beyond reach for most rural households. By contrast, many types of biomass can be freely collected from the local environment or purchased for significantly less than other fuels. Thus, large-scale fuel switching in rural areas is unlikely to occur until rural economies become substantially more developed. This means that an estimated 40 percent of households will continue to rely on traditional biomass energy, especially fuel wood, to meet their daily cooking needs for years to come. This report is structured according to the directional organization of the study. Chapter two presents an overview of household cooking fuels in Indonesia, including policy changes and other factors that influence fuel choices. Chapter three examines an array of stove supply side issues, including market and production capacity, popular stove models, limitations of business models, key features of the supply chain, and attitudes toward new stoves. Chapter four identifies gaps in policies and institutional strengthening that future intervention programs will need to fill and reviews lessons from successful programs promoting clean cooking solutions that can be applied to those focused on clean biomass cooking. Finally, chapter five presents the recommended implementation strategy, including an innovative financing approach, and the next steps in helping Indonesia move toward universal access to clean cooking solutions by 2030.